(untitled) (Proceeding of SINERGY, 2026)
This research was conducted to analyze how compensation, work discipline, work motivation, and work ethic influence employee productivity at PT Royal Korindah Purbalingga. The study involved a total workforce of 395 individuals, from which 219 participants were chosen through a proportionate stratified random sampling technique. The collected data were processed using multiple linear regression supported by SPSS software. The findings reveal that each independent variable, both individually and collectively, exerts a positive and statistically significant impact on employee productivity. The determination coefficient further indicates that a considerable share of productivity variation can be explained by these variables, while the remaining portion is affected by other elements beyond the scope of this research. These results underline that productivity enhancement depends on comprehensive human resource management efforts, particularly through equitable compensation practices, firm disciplinary implementation, reinforcement of employee motivation, and the development of strong work values. In practical terms, management is encouraged to prioritize transparent pay structures, consistent rule enforcement, motivational incentive systems, and the creation of a supportive organizational culture to optimize employee performance. For future investigations, it is suggested that additional aspects such as the work environment, workload, employee competence, career advancement opportunities, and organizational culture be incorporated to achieve a broader and more holistic understanding of productivity drivers.